2019
DOI: 10.3389/fmicb.2019.02217
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Copper-Related Proteomes and Lifestyles in β Proteobacteria

Abstract: Copper is an essential transition metal whose redox properties are used for a variety of enzymatic oxido-reductions and in electron transfer chains. It is also toxic to living beings, and therefore its cellular concentration must be strictly controlled. We have performed in silico analyses of the predicted proteomes of more than one hundred species of β proteobacteria to characterize their copper-related proteomes, including cuproproteins, i.e., proteins with active-site copper ions, copper chaperones, and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 81 publications
1
19
0
Order By: Relevance
“…Loss of copper homeostasis systems in B. pertussis. Comparative genomic analyses revealed that the exclusively human pathogen B. pertussis and its close relative B. bronchiseptica share common sets of copper-homeostasis genes, including genes coding for a CopA ATPase, a PcoA-PcoB-type MCO system, and CopZ, CopI, and CusF copper chaperones, but both lack cusABC genes 18 . A copper storage protein (csp) gene is present in the B. bronchiseptica but not in the B. pertussis genome 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of copper homeostasis systems in B. pertussis. Comparative genomic analyses revealed that the exclusively human pathogen B. pertussis and its close relative B. bronchiseptica share common sets of copper-homeostasis genes, including genes coding for a CopA ATPase, a PcoA-PcoB-type MCO system, and CopZ, CopI, and CusF copper chaperones, but both lack cusABC genes 18 . A copper storage protein (csp) gene is present in the B. bronchiseptica but not in the B. pertussis genome 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they have developed large resistance arsenals against copper intoxication. Conversely, bacteria with restricted ecological niches, such as pathogens or commensals, appear to have fewer copper homeostasis genes 18 . Here, we investigated copper homeostasis in the whooping cough agent Bordetella pertussis, a predominantly extracellular pathogen whose sole natural niche is the human upper respiratory tract 19 .…”
mentioning
confidence: 99%
“…The transcription of genes or operons involved in Cu export are generally activated when excess Cu is detected in the cytoplasm or periplasm. Transcriptional regulators of the MerR, ArsR, or CsoR families [ 6 , 252 , 290 ] sense Cu in the cytoplasm, while two-component systems such as CusRS or CopRS monitor the periplasmic Cu pool. The periplasmic and cytosolic Cu sensing systems can be independently activated, which probably allows for the prevention of Cu toxicity in the respective compartments [ 252 ].…”
Section: Copper Export Across the Cytoplasmic Membranementioning
confidence: 99%
“…Furthermore, human macrophages pump copper into their phagosomes after engulfing pathogenic bacteria to induce oxidative stress and bacterial cell death [ 4 ]. Consequently, bacteria have to deal with high copper concentrations in order to evade the host immune system [ 4 , 5 , 6 , 7 ]. The importance of Cu detoxifying systems for bacterial virulence is exemplified by the observation that the inactivation of Cu-exporting P 1B -type ATPases in Mycobacterium tuberculosis impairs their ability to proliferate in host macrophages [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that the bacterial lifestyle shapes their copper-related proteome, and this is particularly observed in systems involved in copper homeostasis (Antoine et al, 2019). The soil bacterium Cupriavidus necator, which is a predator extraordinarily resistant to copper, uses a toxic copper-binding peptide to kill the actinomycete Agromyces ramosus (Casida, 1987(Casida, , 1988, and its predatory activity against B. subtilis increases after exposure to copper in a concentrationdependent manner (Seccareccia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%